Respiratory symptoms and pulmonary function in male wooden furniture workers exposed to wood dust in Kota Bharu, Kelantan - Sidek, Mohd Yusof (2006)
INTRODUCTION: Wood industries such as wooden furniture factory are one of the major socio-economic development of rural Kelantan. There are significant proportions of workers involved m wooden furniture factories. Majority of factories are lack of supervision by DOSH and have low compliance of the OSHA 1994 and its regulations. COPD and smoking are the leading causes of morbidity and mortality in industrialized and developing countries. Prolonged occupational exposure to wood dust at workplace can increase susceptibility of developing COPD in future. OBJECTIVES: This research ts aimed to study respiratory symptoms, level of knowledge, attitude and practice in relation to wood dust exposure and factors associated with respiratory function in male wooden furniture workers in Kota Bharu, Kelantan. METHODS: A comparative cross-sectional study of 97 male wooden furniture (exposed) workers and 97 male office workers (non-exposed) was conducted from May till July 2005. Data was collected through a questionnaire on respiratory symptoms, knowledge,attitude and practice of health hazards of wood dust exposure m workplace and spirometry test. Chi-square test was used to determine the significant difference in the prevalence of respiratory symptoms and independent t test was used to compare means ofKAP score and result of respiratory function parameter between exposed and nonexposed group. Multiple linear regression was used to determine factors associated with FEY 1 in exposed group. RESULTS: The prevalence of respiratory symptoms were significantly higher among exposed compared to non-exposed group. The most frequent symptoms among exposed group were skin itchiness (47.4%), followed by chest tightness (39.2%), morning cough (35.1 %) and morning phlegm (35.1 %). The mean total knowledge score in exposed group was significantly lower [95 .7(10.8)] compared to non-exposed group [99.8( 10.3)]. Exposed group had significantly higher mean score for total practice score [24.8( 4.8)] compared to non-exposed group [22.2(4.7)]. There were no significant differences for mean total attitude and KAP scores between exposed and non-exposed group. About 71% of exposed group had abnormal respiratory function whereas only 24% of non-exposed group had abnormal respiratory function. Of the 69 (71.1%) exposed group with abnormal spirometry test, 30 (30.9%) exhibited mild restriction, 24 (24.7%) with moderate restriction and 15 (15SYo) with severe restriction. Duration of smoking (p<O.OO I), height (p<O.OO 1 ), duration of work (p=0.002) and number of cigarettes smoke perday (p=<O.OOl) were significantly related to FEV1 and FVC. Only age (p=0.049) was significantly related to FEV1/FVC. CONCLUSIONS: We therefore conclude that the level of knowledge, attitude and practice in relation to the health hazards of wood dust exposure in the exposed group was unsatisfactory compared to the non-exposed group and chronic occupational wood dusts exposure can lead to higher prevalence of respiratory symptoms and abnormal respiratory function among exposed group.